2006
DOI: 10.1210/en.2005-0596
|View full text |Cite
|
Sign up to set email alerts
|

Demilune Cell and Parotid Protein from Murine Oviductal Epithelium Stimulates Preimplantation Embryo Development

Abstract: In mammals, fertilization and early preimplantation embryo development occur in the oviduct. We hypothesized that interaction exists between the developing embryos and the maternal genital tract, such that the embryos modulate the physiology and gene expression of the oviduct so that it is conducive to their development. By comparing the gene expression patterns in mouse oviducts containing transferred preimplantation embryos with those of oviducts containing oocytes, we report here the characterization of dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 57 publications
0
30
0
1
Order By: Relevance
“…In addition, transcription factor Sp1, which is essential for early embryonic development (67), was down-regulated in Cnr1 Ϫ/Ϫ and Faah Ϫ/Ϫ blastocysts by 76 and 42%, respectively. Notably, expression of Dcpp1 (68) and Hormad1 (69), which play roles in embryo development, was also lower in Cnr1 Ϫ/Ϫ and Faah Ϫ/Ϫ blastocysts.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, transcription factor Sp1, which is essential for early embryonic development (67), was down-regulated in Cnr1 Ϫ/Ϫ and Faah Ϫ/Ϫ blastocysts by 76 and 42%, respectively. Notably, expression of Dcpp1 (68) and Hormad1 (69), which play roles in embryo development, was also lower in Cnr1 Ϫ/Ϫ and Faah Ϫ/Ϫ blastocysts.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Lee et al (2005Lee et al ( , 2006 have analyzed the interaction between embryos and oviduct in mice and their results suggested that the presence of the embryo could affect the protein expression of the mouse oviductal epithelium, as shown for the phospholipid transfer protein (PLTP) and the demilune cell and parotid protein.…”
Section: R7mentioning
confidence: 99%
“…Using subtractive suppression hybridization, differential expression of a panel of genes including phospholipid transfer protein (Lee et al, 2005) and demilune cell parotid protein (Lee et al, 2006) were demonstrated between oviducts containing preimplantation embryos and those containing oocytes (Lee et al, 2002). It is not known whether preimplantation embryos would influence the production of oviductal C3.…”
Section: Introductionmentioning
confidence: 99%